Approaches to the Synthesis of a Water‐Soluble Carboxy Nitroxide. Issue 5 (8th January 2013) - Thomas, Komba; Chalmers, Benjamin A.; Fairfull‐Smith, Kathryn E.; Bottle, Steven E.
Abstract: The robust and diversely useful isoindoline nitroxide, 5‐carboxy‐1, 1, 3, 3‐tetramethylisoindolin‐2‐yloxyl (1 ; CTMIO), has previously been synthesised in low‐to‐moderate yields from phthalic anhydride (3 ). Recent interest in its biological potential as a potent antioxidant and in other areas has seen an increased demand for its production. Herein, three new synthetic routes to CTMIO are presented and their efficiencies assessed. Two routes, via the nitrile9 and the formyl compound11, derive from 5‐bromo‐1, 1, 3, 3‐tetramethylisoindoline (6 ). The third approach starts from the readily accessible starting material, 4‐methylphthalic anhydride (12 ), and proceeds by a methylarene oxidation with potassium permanganate. The three new approaches yield CTMIO in comparable overall yields (16–18 %); however, the synthetic efficiency is most improved when employing the nitrile intermediate9 . Abstract : Several synthetic approaches to an important water‐soluble nitroxide antioxidant are described. Each provides the final product in a comparable overall yield, however, the copper‐mediated cyanation of an aryl halide followed by hydrolysis employs the fewest steps and provides the greatest synthetic convenience.